2018
DOI: 10.3201/eid2408.170334
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Peste des Petits Ruminants Virus, Georgia, 2016

Abstract: A phylogenetic analysis of samples taken from reported outbreaks of peste des petits ruminants virus (PPRV) in Georgia revealed a closer relationship to viruses from northern and eastern Africa than to viruses from countries closer to Georgia. This finding has crucial implications for the control of PPRV in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…In summary, the results of this study indicate that the PPRV involved in the reported outbreak in Burundi is related to the PPRV lineage III circulating in the East Africa region. Transboundary movements of infected animals might be at the origin of this outbreak, as has been described in several countries both in Asia (Muthuchelvan et al, ; Shatar et al, ) and Africa (Boussini et al, ; Dundon et al, ) although not always with clear explanations (Donduashvili et al, ). The control and regulation of such animal movements will assist in the control and management of PPRV as attempts are made to eradicate the disease globally by 2030.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In summary, the results of this study indicate that the PPRV involved in the reported outbreak in Burundi is related to the PPRV lineage III circulating in the East Africa region. Transboundary movements of infected animals might be at the origin of this outbreak, as has been described in several countries both in Asia (Muthuchelvan et al, ; Shatar et al, ) and Africa (Boussini et al, ; Dundon et al, ) although not always with clear explanations (Donduashvili et al, ). The control and regulation of such animal movements will assist in the control and management of PPRV as attempts are made to eradicate the disease globally by 2030.…”
Section: Resultsmentioning
confidence: 76%
“…Peste des Petits Puminants (PPR) is a highly contagious viral disease of small ruminants which was first described in Côte d'Ivoire (Gargadennec & Lalanne, ) and has now been reported in many parts of Africa, the Middle East, Eurasia (Bulgaria, Georgia and Turkey) and Asia (Donduashvili et al, ; Libeau, Diallo, & Parida, ; Parida et al, ). The PPR virus (PPRV) belongs to the genus Morbillivirus within the Paramyxoviridae family (Gibbs, Taylor, Lawman, & Bryant, ) and causes a disease which is characterized by high fever, ocular‐nasal discharge, stomatitis, diarrhoea and pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…PPR was first reported in 1942 in Ivory Coast, West Africa [ 6 ]. Since then, it has spread across northern and sub-Saharan Africa into Asia and has now been reported in over 70 countries in Africa, the Near and Middle East, and Central and Eastern Asia [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ], including Georgia in 2016 [ 14 ] and Bulgaria in 2018 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…PPRV was first reported in Ivory Coast (Cote d'Ivoire) of West Africa in 1942 (8). Now, the disease has spread in Central and East Africa, the Middle East, Turkey, China, India, and Nepal, reaching Europe's doorstep with cases reported in Morocco (9), Turkey (10), and Georgia (11). If left uncontrolled, it will spread even further, causing massive loss and hardship for millions of farmers and herders.…”
Section: Introductionmentioning
confidence: 99%